Determinación de impactos a la calidad del agua, mediante bioindicadores (macroinvertebrados), producidos por las descargas hídricas de la estación Secoya en el rio Granito de la parroquia Pacayacu del cantón Lago Agrio - Villavicencio Castillo, María Alexandra (2015)
The main objective of this research was to evaluate the water quality of the River Granite, for liquid discharges produced in Redwood station operated by PETROAMAZONAS EP, to do physical-chemical analysis was performed and used biomarkers (macroinvertebrates), as indicators of water quality, in order to make a comparative analysis. For analyzes physical-chemical samples were run on four points, based on the parameters established in the Executive Decree 1215 (RAOHE) Table 4a and 4b which are pH, TPH, ST, COD, EC, barium, lead, vanadium and chromium. The methodology for the assessment of macroinvertebrates as indicators of water quality was developed based on BMWP / Col index. The results of physical-chemical analysis reflected that the pH was outside the permissible limit in paragraphs 3 and 4 with values of 8.08 and 5.29, respectively, also the total hydrocarbons in their results showed that exceed the standard values 87.5 mg / l and 25.0 mg / l in points 1 and 2 respectively. In monitoring macroinvertebrates in three sampling points 187 macroinvertebrates distributed in 7 orders and 10 families, determined as water of dubious origin in points 1 and 2 and acceptable in point 3. He finally made it identified an environmental management plan to prevent and mitigate pollution in the waters of Granite River.